THE CONCEPT AND CHARACTERISTICS OF THREATS TO THE FINANCIAL SECURITY OF SYSTEMICALLY IMPORTANT BANKS - Lytvynenko О. (Socio-economic relations in the digital society, 2021)
The low level of confidence in banks and the slow pace of its recovery exacerbate the problem of financial security of banking institutions. The low level of financial security of even one systemically important bank can provoke disruption and deformation of the banking sector as a whole. The effectiveness of building the entire system of financial security of systemically important banks depends on the completeness of determining the concept of threats, assessing the level of their intensity and possible consequences of the impact. In the article particular attention is paid to the disclosure of theoretical aspects of the concept of threat to financial security of systemically important banks. In particular, the essence and differences between the concepts of «threat to financial security», «factors of financial security», «danger to financial security», «challenge to financial security» and «damage to financial security» within the study of financial security of systemically important banks are given. The author’s definition of the threat to the financial security of systemically important banks is given, according to which the threat to the financial security of systemically important banks should be considered as a realized form of danger, a set of factors and phenomena that cause disruption and reduce, that can provoke destabilization of the entire financial system. The article considers the main approaches to the classification of threats to the financial security of systemically important banks. It was found that the division of threats by source of origin is fundamental, according to which they can be divided into external and internal (exogenous and endogenous). A detailed description of external and internal threats to financial security of systemically important banks is given. In the context of the study of financial security of systemically important banks, the issue of public confidence was studied. It was found that a stable level of confidence is a factor in ensuring financial security, and reducing the level of public confidence should be considered as one of the main threats to the financial security of systemically important banks.